Czech Places of Remembrance between Legacy and Tradition - Olšáková, Doubravka (Dějiny – teorie – kritika, 2012)
In her essay, the author considers various approaches to the notion of places of remembrance (lieux de mémoire) which were applied in Czech historiography since 1980s. Using analysis of works written within the context of the journal “Husitský Tábor“, the Pilsen symposia, as well as independent attempts at describing places of remembrance such as those authored by Vladimír Macura, Eduard Maur, or Vít Vlnas, the author concludes that the concept referred to by West European historians as ‘lieux de mémoire partagés’ (shared places or memory) is – probably due to a strong and traditional orientation on nationally Czech history – still rather removed from the main focus of interest of Czech historians and even remains relatively unknown.